The Confederazione Italiana Archeologi social media projects during the Covid-19 pandemic in Italy: changing the digital communication approach to the online community. - Donati, Nicolò; Gusberti, Elisa; Magliaro, Tommaso; Riva, Alessandra (Ex Novo: Journal of Archaeology, 2021)
With the onset of the Covid-19 pandemic, social media has rapidly become a crucial communication tool for sharing information with the public. In this article, we shall examine two media projects: #CIAndremo and Una domenica al museo launched on the social media pages of the CIA - Confederazione Italiana Archeologi following the lockdown stages in Italy in 2020. #CIAndremo is the first original project that our association released on Facebook, Instagram IGTV and YouTube during the pandemic, responding to the social campaign #iorestoacasa (I stay at home) as a measure to contain the epidemic outbreak. We will present the methods and procedures used to produce the videos, the limitations we faced because of the lockdown and the final positive feedback received from the public. The second project was the enhancement of Una Domenica al Museo (Sunday at the Museum), a weekly column born on the CIA Instagram profile, which is advertised with the hashtag #unadomenicaalmuseo. Here we are presenting the adaptation of the format that followed the Italian government lockdown restrictions and how it also changed the interaction with the public.